Affective encounters: enchantment and the possibility of reading for pleasure. (25th March 2018) - Burnett, Cathy; Merchant, Guy
Abstract: Discourses of reading for pleasure have seldom addressed the multiple and complex digital media practices of children and young people or the changing nature of literacy. This article explores the affective encounters that are generated in the relations between readers, digital texts and things by applying Bennett's notion of enchantment. Using examples of everyday literacies, it considers the diversity of ways in which such encounters manifest, noting how such practices are located within intersecting continua ranging from immersive to lightweight, sustained to ephemeral, individual to collective, serious to flippant and from momentary hilarity to deep engagement. The article outlines some implications of enchantment for thinking about reading for pleasure in education focusing on the importance of potentiality and relationality.